EP 38. Subthalamic nucleus Deep Brain Stimulation (STN-DBS) reduces freezing of gait in Parkinson's disease in the VANTAGE prospective, multi-center trial. Issue 9 (September 2016) - Barbe, M.T.; Stummer, C.; Van Dyck, N.; Jain, R.; Chen, L.; Reker, P.; Brücke, T.; Seijo, F.; San Martin, E. Suarez; Haegelen, C.; Verin, M.; Amarell, M.; et al.
Abstract : Background: Deep Brain Stimulation (DBS) is effective for Parkinson's disease (PD) symptom relief; however, improvement of freezing of gait (FOG) remains under debate. Some studies indicate STN-DBS alleviates FOG, while others suggest an association of STN-DBS with worsening of gait and balance or even induction of FOG. The VANTAGE study assesses motor improvement in moderate-to-severe PD following bilateral STN-DBS using a new, implantable, rechargeable, multiple-source, 16-output (supporting two 8-contact leads), constant-current, CE-marked DBS System. We report the effects of STN-DBS on FOG in this cohort of PD subjects. Methods: VANTAGE is a monitored, prospective, multi-center, non-randomized, open-label interventional trial, sponsored by Boston Scientific Corporation. FOG was characterized with UPDRS-II item 14, the freezing of gait questionnaire (FOGQ) and a walking test known to provoke FOG pre and post-surgery. Data collection included FOGQ at Baseline and 26 weeks post-implantation, and the walking test at Baseline, 12, 26, and 52 weeks post-implantation. The walking test was videotaped and rated remotely by an independent rater (CS), blinded to the subject's implantation status. Results: Thirty-eight subjects, of the forty implanted, were analyzed with FOGQ data. The FOGQ showed significant improvement at 26 week follow up versus baseline derived from UPDRS-III item 29 and UPDRS II item 14. FOGQ (item 3) data at 26 weeks versus baseline indicated 12 freezers remained freezers, 15 freezers turned to non-freezers, 10 non-freezers remained non-freezers, and one non-freezer turned to a freezer. The walking test was performed by 29 of 38 subjects at baseline during medication off. Thirteen subjects showed FOG-episodes off medication at baseline and improved after L-Dopa intake. Postoperatively, the total walking time, FOG episode occurrences, and total time spent frozen were reduced at week 12, 26, and 52 compared to baseline during medication off. Conclusions: FOGQ and walking test data demonstrate that STN-DBS can reduce FOG occurrence and severity at 26 weeks postoperatively with constant effects at week 52. Follow-up data will help to understand if improvement on FOG persists long term.